Exploring instructional leadership practices of primary school heads in the context of increased accountability in the Lubombo region, Eswatini - Matsenjwa, Ncamsile (My University, 2022)
This study explored instructional leadership practices of primary school heads in the context of increased accountability in the Lubombo Region of Eswatini. A mixed methods design had been employed in the study, wherein the sequential exploratory design was adopted with the pragmatist paradigm. Within the first phase, semi-structured interviews, document analysis and observations were used for collecting data. In the second quantitative phase, structured questionnaires were used, while, in the last phase, a focus group interview and semi-structured interviews were carried out. The population of the study consisted of 153 educational professionals in the Lubombo Region of Eswatini. Purposive sampling, systematic sampling, simple random samplings were techniques engaged in selecting the different participants. The majority of the head teachers in rural primary schools have misconceptions regarding their roles as instructional leaders. Consequently, there is a significant gap between policy and practice insofar as instructional leadership in rural primary schools is concerned. The majority of the time of rural school head teachers in the Lubombo Region is consumed by administrative tasks, including meetings and accounting roles, among other routine issues. Head teachers face a number of challenges that restrict them from effectively promoting instructional leadership in schools within the Lubombo Region, including limited instructional resources, overcrowded classes, as well as insufficient time to complete their roles, late hiring of teachers, public participation, teacher unionism, offenders not sanctioned, teachers’ attitudes towards head teachers’ supervision, normal progression policy and drug abuse. Among the coping strategies to manage instructional leadership in the context of increased accountability, head teachers work extra hours and make use of the delegation option of management. Increased accountability for school heads in rural schools is thought to improve overall performance and quality of education. However, this places significant pressure on the head teachers to perform, leading to extremely stressful events. It is recommended that the Ministry of Education and Training launches capacity-building programmes aimed at educating head teachers about instructional leadership. Considering the excess times spent on administrative tasks, it is suggested that the official responsibilities of a standard head teacher be audited by the Regional Education Office. There may be the need for the MoET to invest more in rural schools, to ensure adequate instructional resources are available for use. It may be essential for the MoET to focus on policies and procedures that promote the notion of increased accountability. Official standard appraisal forms for school heads to utilise during classroom observation should be designed by the MoET.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022